Anti-herpes simplex virus type 2 activity from Rhinacanthus nasutus (Linn.) Kurz. extracts as affected by different extraction solvents - Benchaluk Thongchuai (2019)
© 2014 Chiang Mai University. Rhinacanthus nasutus (Linn.) Kurz. is a medicinal plant traditionally used in northern Thailand. It has anti-bacterial, anti-inflammatory, anti-cancer, and anti-viral properties. This study investigated the anti-herpes simplex virus type 2 (anti-HSV2) activity of stem extracts of R. nasutus (Linn.) Kurz. on American green monkey kidney (or Vero) cells. The plant extracts were prepared with six different solvents: ethanol, ethylacetate, methanol, dichloromethane, acetone and hexane. The cytotoxicities of the stem extracts were determined using MTT assay with various concentrations of the stem extracts (2.44 to 156 μg/mL) and the 50% cytotoxicity dose (CD 50 ) was calculated after the Vero cells were treated with the stems extracts for 24 h. The methanolic extract showed a low cytotoxicity on the Vero cells, with a CD 50 value of 78.22 ± 23.54 μg/mL; in contrast, the ethylacetate, dichloromethane, acetone and hexane extracts were highly toxic to the Vero cells. The anti-HSV2 activities of the plant extracts were investigated by plaque reduction assay after treating the infected Vero cells for 24 h with the stem extracts at concentrations between 2.44 and 19.50 μg/mL. The inhibitory effect values of the 50% effective dose (ED 50 ) were determined. The methanolic extract had the highest inhibitory effect (ED 50 of 16.16 + 10.83 μg/mL) against HSV-2 infections and inhibited HSV-2 particles by 70.5% after 24 h of treatment. Our results showed the potential for using methanolic extracts from the stem of R. nasutus (Linn.) Kurz. to treat HSV2 infections during the late stage viral life cycle 24 h after infection.